Blockchain, smart contracts, and commercial arbitration through an ODR: reflections on a new approach to dispute resolution - Rodríguez Palacios, Tania del Socorro (DIXI, 2024)
E-commerce, new technologies, and dispute resolution methods have changed; consequently, legal business and service provision have also evolved. However, relationships stemming from smart contracting and Online Dispute Resolution (ODR) are not exempt from the issues surrounding their lack of explicit regulation. This research first addresses the generalities of blockchain, smart contracts, and ODR, followed by reflections on the relationship between them. Despite lacking widespread and uniform regulation, these new technologies have been applied for some time now. Therefore, the aim is to highlight their union and impact in the field of legal science, to demonstrate how commercial arbitration through ODR represents the best option for resolving disputes arising from blockchain technology and smart contracts, thanks to their characteristics such as decentralization, flexibility, agility, immediacy, and specialization, qualities that align with the legal and electronic essence of both figures.